HUBUNGAN TINGKAT PENDIDIKAN, UMUR, DAN MASA KERJA DENGAN TINGKAT PENGETAHUAN KESEHATAN GIGI DAN MULUT PADA GURU PENJASKES SD DI KECAMATAN TAMPAK SIRING GIANYAR - IGA Ayu Dharmawati; I Nyoman Wirata (Jurnal Kesehatan Gigi (Dental Health Journal), 2016)
Knowledge is the result of know and this occurred after people perform sensing on a particular object. Factors affecting knowledge of factors including internal, external and learning approach. In addition to these three factors one's knowledge is also influenced by education, age, and tenure. Knowledge of dental care will increase if the role of educators in schools. One effort to improve oral health knowledge, the role of a primary school PE teachers to deliver to elementary students is expected. This study aims to determine the relationship between the level of education, age and years of elementary school PE teacher in Tampaksiring district, Gianyar. The method used by means of an observational survey on 31 PE teachers, with Spearman analysis. From the analysis results obtained by the significant correlation (0.037 0.05) between level of education and level of knowledge.And no significant relationship between the level of knowledge with age (0.618 0.05) and the level of knowledge with tenure (0.596 0.05).The conclusion of this study, the majority of primary school PE teachers in Tampaksiring district has a bachelor's level education with an excellent level of knowledge. It is advisable to conduct training dental health education on a regular basis to improve the knowledge of primary school PE teachers throughout the Tampaksiring district, Gianyar